Inter‐relay interference suppression for two‐path MIMO relay systems. Issue 9 (4th April 2016) - Rui, Xianyi; Wang, Mengmeng; Liu, SuQi
Abstract : A two‐path multiple‐input multiple‐output (MIMO) relay system is addressed, in which the inter‐relay interference (IRI) between two relays leads to deterioration of system performance. Transmit and receive weight vectors are employed for suppressing the IRI. Maximising the ratio between the power of the desired signal to the IRI power at the relay reception and transmission and forming a criterion function for jointly calculating the optimal receive and transmit suppression vectors, respectively. Simulation results show that the proposed scheme can improve the system performance.